EMPOWERING THE ROLE OF MOTHERS THROUGH SELF-SUFFICLENCY TRAINING IN PROCESSED ANCHOVY SAUSAGES (Stolephorus spp.) IN FAMILY COMMUNITIES WITH CHILDREN WITH SPECIAL NEEDS â€œKURNIA ILAHIâ€ IN METESEH SEMARANG - Endah Aryati Ekoningtyas; Ani Subekti; Muflihah Isnawati; Benni Benyamin (Poltekkes Kemenkes Semarang, 2023)
Physical limitations and intelligence of children with special needs (ABK) cause a lack of maintenance of oral health. Maintenance of dental and oral health that is less than optimal causes children with special needs to experience problems with their teeth and mouth (dental caries). The high prevalence of dental caries causes the masticatory function is not optimal. Dental caries can be prevented by sufficient calcium and fluoride in the teeth, such as the consumption of anchovies. So there is a need for training in the manufacture of processed anchovy sausages for mothers of children with special needs